20 seasons : Broadway musicals of the 21st century - Osatinski, Amy S. (Amy Sara) (Routledge, 2024)
"20 Seasons: Broadway Musicals of the 21st Century catalogues, categorizes, and analyzes the 269 musicals that opened on Broadway from the 2000-2001 season through the 2019-2020 season. This book is the first to comprehensively examine the musicals that premiered on Broadway during this important historical period, which was bookended by the 9/11 terrorist attacks on one end and the Coronavirus pandemic on the other. It begins by exploring the historical context for the first 20 years of the 21st century and how this impacted American culture and theatre. Rather than chronologically, the musicals are then organized into categories based on their source material and whether they were original musicals or revivals, painting a detailed picture of the Broadway musical in first 20 years of the 21st century. Jukebox Musicals, Screen-to-Stage Musicals, Revivals, and Original Musicals are all covered, and each chapter ends with reading guides and discussion prompts. The book not only discusses what was produced, but by whom, uncovering the stark lack of representation for women and artists of color on Broadway musical creative and design teams. Additionally, the last chapter discusses the Coronavirus pandemic, the Broadway shutdown, and what happened to the Broadway musical during the shutdown, including the response to the Black Lives Matter Movement in the summer of 2020. 20 Seasons: Broadway Musicals of the 21st Century will appeal to fans and scholars of musical theatre, as well as students of Musical Theatre, Musical Theatre History, American Studies, and Pop Culture Studies"--